AN ASSOCIATION OF METABOLIC SYNDROME WITH NONALCOHOLIC FATTY LIVER DISEASE - JAIN, SHWETA; SS, BISWAS; JAIN, SWATI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Nonalcoholic fatty liver disease is strongly linked with hepatic fatty infiltration and visceral adiposity, therefore, being a cause and a result of metabolic syndrome. The objective of the study is to find an association of metabolic syndrome (MetS) with nonalcoholic fatty liver disease (NAFLD). Methods: A total of 342 subjects from which 86 NAFLD 86 control were suitably selected for study duration of 1 year. Diagnosis of nonalcoholic fatty liver disease was done by liver imaging and based on liver enzymes. MetS assessment was done by the national cholesterol education program adult treatment panel III (NCEP ATP III) criteria. Estimation of all biochemical and hematological parameters and liver enzymes was done following standard guidelines. Mean comparison of quantitative data in different groups was analyzed with one-way analysis of variance. Results: There were significant high levels of body mass index, waist circumference, and lipid profiles in NAFLD patients in comparison to control population (p<0.001). According to the NCEP ATP III criteria, 59.3% of NAFLD were present with MetS where risk estimate was significant (odds ratio=2.15). Conclusion: This study suggests that there is an increased in all the components of MetS and gross changes in biochemical markers in cases of NAFLD. Therefore, whenever MetS factors are met in the clinical checkups, patients must be diagnosed for NAFLD by imaging (fatty liver).